Efficacy of netakimab in key psoriatic arthritis domains: 54-week results from the phase III BCD-085-8/PATERA study - T. V. Korotaeva; V. I. Mazurov; A. M. Lila; I. Z. Gaydukova; A. L. Bakulev; A. V. Samtsov; V. R. Khairutdinov; A. V. Zinkina-Orikhan; Yu. A. Sevastyanova; A. V. Eremeeva (Научно-практическая ревматология)
Netakimab is a humanized anti-interleukin-17А monoclonal antibody approved for the treatment of psoriatic arthritis, ankylosing spondylitis, moderate to severe psoriasis. Herein, we report the accumulated efficacy data and safety findings of 54-week netakimab treatment during the PATERA study.The aim of the study was to assess the long-term efficacy and safety of netakimab in patients with active psoriatic arthritis.Materials and methods. 194 patients with active psoriatic arthritis despite the previous therapy with nonsteroidal anti-inflammatory drugs, conventional or biologic disease-modifying antirheumatic drugs were initially randomized to receive 120 mg netakimab or placebo (1:1) at weeks 0, 1, 2, 4, 6, 8, 10, 14, 18, 22. At week 16 inadequate responders in placebo group were reassigned to netakimab in a blinded manner. From week 24 all patients receive open-label netakimab. The analyzed period includes 54 weeks.Results. Netakimab demonstrated sustained treatment response. 94.9% of patients in the netakimab group achieved ACR20 at week 54; 89.5% achieved PASI75 response. Axial disease, dactylitis, and enthesitis significantly improved with netakimab. A similar pattern was observed for placebo/netakimab treated patients. Netakimab was well tolerated. The majority of adverse events were mild and moderate. The most frequent treatment-related adverse events were lymphopenia, increased alanine aminotransferase, hypercholesterolemia. Adverse events of grade 3–4 were observed in 2%.Conclusion. Netakimab demonstrated sustained efficacy in key psoriatic arthritis domains at week 54 with a favorable longterm safety profile.